Aflatoxin B1 Contamination Association with the Seed Coat Biochemical Marker Polyphenol in Peanuts Under Intermittent Drought - Maman Moutari Aminou; Hamidou Falalou; Harou Abdou; Venugopal Mendu (Journal of Fungi)
Aflatoxin B1 (AFB1) contamination (AC) increases as the severity of drought stress increases in peanuts. Identifying drought-tolerant (DT) genotypes with resistance to Aspergillus flavus colonization and/or infection may aid in developing peanuts resistant to aflatoxin contamination in the semi-arid tropics. The goal of this study is to identify DT genotypes with seed coat biochemical resistance to A. flavus infestation and aflatoxin contamination. Experiments were carried out at ICRISAT Sahelian Center; fifty-five genotypes were assessed under adjacent intermittent water-stressed (WS) conditions imposed from the 60th day after sowing to the maturity date and well-watered (WW) conditions in an alpha lattice design with two factors. The yield and its components, the incidence of A. flavus colonization, aflatoxin contamination, and seed coat total polyphenol (SCTPP) were investigated. Our findings show that the water deficit reduced the pod yield, seed yield, and haulm yield by up to 19.49%, 27.24%, and 22.07%, respectively, while it increased the number of immature pods per plant (IMPN) and the aflatoxin contamination by up to 67.16% and 54.95%, respectively. The drought tolerant genotypes ICG 2106, ICG 311, ICG 4684, ICG 4543, and ICG 1415 maintained a high yield, small number of IMPN under WS and low aflatoxin content variation between WW and WS. Our findings revealed that in the drought-tolerant genotypes ICG 1415, ICG 2106, ICG 311, ICG 4684, and ICG 4543, there was a significant relationship between the aflatoxin resistance and the seed coat total polyphenol under the two water treatments (r2 = 0.80; r2 = 0.82). This suggests that these drought-tolerant genotypes kept their seed coat intact and minimized the aflatoxin contamination under an intermittent water deficit.